2019
DOI: 10.1371/journal.pone.0224102
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported non-receipt of HIV test results: A silent barrier to HIV epidemic control in Mozambique

Abstract: IntroductionPeople living with HIV (PLHIV) and who are aware of their HIV status can access and benefit from antiretroviral therapy (ART) with subsequent individual and public health benefits; however, many PLHIV are unaware of their HIV status. We assessed the magnitude and determinants of self-reported non-receipt of HIV test results in adults aged 15–59 years old in Mozambique.MethodsWe performed a secondary analysis of data from the 2015 Mozambique Immunization indicators, Malaria and HIV/AIDS (IMASIDA 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…This finding was supported by studies conducted elsewhere. 18 , 21 , 27 Individuals with risky sexual behaviors live under persistent fear and uncertainty about their serostatus and are usually suspicious and worried that they might have infected with HIV, this could have urged them to develop habits of seeking voluntary counseling and testing service. 28 Concerning HIV/AIDS knowledge, pregnant women having higher and comprehensive knowledge about HIV had higher chances of HIV testing compared to women with low knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by studies conducted elsewhere. 18 , 21 , 27 Individuals with risky sexual behaviors live under persistent fear and uncertainty about their serostatus and are usually suspicious and worried that they might have infected with HIV, this could have urged them to develop habits of seeking voluntary counseling and testing service. 28 Concerning HIV/AIDS knowledge, pregnant women having higher and comprehensive knowledge about HIV had higher chances of HIV testing compared to women with low knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Even though HIV testing is very crucial for all strategies related to care, prevention and treatment of HIV/AIDS, it is less practiced among reproductive-age women, particularly in developing countries [ 6 , 16 ]. Every individual needs to know their HIV status for the benefit of themselves and others [ 1 , 20 , 21 ]. Although global efforts had made to reduce the spread of HIV/AIDS, its testing coverage remains low in developing countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lightfoot et al reported that using a social network strategy to distribute HIV self-test kits could reduce undiagnosed infections [ 19 ]. This suggested that factors such as age, residence, and education level should also be taken into consideration to develop more targeted promotion testing strategies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%